Fixed Point Theorems for Weakly Contractive Maps in Banach Spaces - Aneke, S. J. (Communications in Mathematics and Applications, 2012)
In this paper, we prove fixed point theorems for certain classes of mappings called weakly contractive. These mappings were introduced by Alber and  Guerre-Delabriere [1] and studied by the author and others via iterative processes [1, 2].
Keywords: Fixed point; Weakly contractive; d-weakly contractive; Strict contraction; Uniformly smooth spaces